Profiling the diets of Classic Maya communities living in Southeastern Petén through stable isotope analysis - Gloria Ivonne Hernández Bolio; Nadia Neff; Keith Prufer; Patricia Quintana; Viorel Atudorei; Mara Reyes; Lilian Corzo; Vera Tiesler (PLoS ONE, 2026)
During the Early and Late Classic periods (250–900 CE), Maya communities in southeastern Petén experienced rapid demographic growth, and organized themselves here not as centralized city states but as a network of complex, small-scale polities. As documented by the Archaeological Atlas of Guatemala (IDAEH), this area encompasses more than 400 registered sites across the northwestern Maya Mountains, several river basins, and humid savannas, and therefore offers a diversified ecological and cultural setting for exploring local subsistence strategies of the era. Excavation and sampling strategies targeted non-elite burials, providing a unique opportunity to reconstruct the diets of commoner populations on a regional scale, especially given that no prior isotopic research has been conducted in this vast area. For this study, we analyzed stable carbon (δ 13 C) and nitrogen (δ 15 N) isotopes from human bone collagen and δ 13 C from dental enamel carbonate to evaluate collective food selection, composition, and variability over time, as well as potential social or environmental influences. We contextualized these with the isotopic profiles in published research that covers the more hierarchically organized urban centers from other parts of the Maya area. Our own results reveal consistent maize-based diets that were likely supplemented by other plant-based foods and terrestrial animal resources, with inter-site differences reflecting local social and ecological contexts. Variation in isotopic values by age and the presence of skeletal modifications suggest that life-history and biocultural factors shaped dietary patterns. Overall, our findings demonstrate an increasing reliance on maize towards the end of the Classic period and even beyond the hegemonial collapse. Taken together, our findings in southeastern Petén’s populations expand our understanding of subsistence diversity and diet among non-elite Classic Maya populations.